PENGARUH KOMPETENSI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (STUDI PADA BIRO PENGADAAN BARANG/JASA PEMERINTAH SETDA PROVINSI SULAWESI TENGGARA) - Pricilia Christina Angel; Juharsah; Sinarwati; Dzulfikri Azis Muthalib (JITAA : Journal Of International Taxation, Accounting And Auditing, 2026)
This study is motivated by the importance of human resource management in improving employee performance at the Government Procurement Bureau of the Regional Secretariat of Southeast Sulawesi Province. Employees are required to have adequate competence in dealing with job complexity and changes in government procurement regulations. High workload can also affect job satisfaction and employee performance. This study aims to analyze the effect of competence and workload on employee performance with job satisfaction as a mediating variable. The study used a saturated sampling (census) method and was analyzed using PLS-based SEM with SmartPLS 4.0. The results indicate that job satisfaction is able to mediate the effect of competence and workload on employee performance. Competence and job satisfaction have a positive and significant effect on employee performance, while workload has a negative and significant effect.